Housing Security and Land Ownership under Pradhan Mantri Awaas Yojana–Gramin (PMAY-G): Assessing Rural Development Outcomes in Tamil Nadu - Dr. N. RAMESHKUMAR; Mr. T. SATHISPRABU. M.A., M.Phil. SET., Ph.D; Mr. R. VENKATESH. M.A., Ph.D (PT. Radja Intercontinental Publishing, 2026)
Housing security and secure land ownership are fundamental components of sustainable rural development, social protection, and poverty reduction. The Pradhan Mantri Awaas Yojana–Gramin (PMAY-G), launched in 2016, seeks to provide permanent housing to eligible rural households while promoting dignity, asset creation, and inclusive growth. In Tamil Nadu, the implementation of PMAY-G has been strengthened by the state's long-standing commitment to welfare-oriented housing policies and decentralized rural governance. This study assesses the effectiveness of PMAY-G in enhancing housing security and land ownership and examines its contribution to rural development outcomes in Tamil Nadu. The programme has strengthened household asset ownership and promoted women's empowerment through joint or exclusive ownership of residential property. Beneficiaries have experienced improved access to sanitation, safe drinking water, electricity, and other essential services, leading to better health outcomes, educational opportunities, and enhanced quality of life.